PERAN HUMAS KORPS DA’I DEWAN MASJID INDONESIA DALAM MELAKSANAKAN KEGIATAN BHAKTI SOSIAL - Marye Vaya Nurrachim (Jurnal Visi Komunikasi, 2016)
The role of public relations in designing social bhakti activities to get a positive image of the community is a top priority for this organization. Here the researcher tries to examine how the public relations role of the Corps of Da'i Dewan Masjid Indonesia in succeeding the implementation of social welfare bhakti activities and the distribution of basic needs. Four public relations roles are Communication Technician, Communication Facilitator, Expert Advisor, and Problem Solving Facilitator. This research uses descriptive research type, and qualitative research method of case study by conducting in-depth interview to some resource and observation as well as some supporting documents. Based on the result of the research, it can be concluded that the role of public relations officer of Da'i Council of Mosque of Indonesia in social activities of orphanage donation and the distribution of basic foods, the role of public relations done by focusing on the role of communication technician (Communication Technician) and Communication Facilitator.